2017
DOI: 10.1111/tid.12771
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviruses excretion in saliva of pediatric transplant recipients

Abstract: The association found between CMV shedding in saliva and CMV viremia in this study opens the possibility of future studies of using viral load in saliva as a predictor of viremia. The implementation of herpesviral load in saliva samples for early clinical intervention in pediatric recipients needs a study with a large number of samples for further conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
7
2
Order By: Relevance
“…Although those authors suggest the existence of such a relationship, it is not causal. Moreover, they found no relationship between CMV viral load in saliva and active disease 17 . Immunosuppressive protocol, reduced sample size, pediatric patients, type of transplantation (renal and hepatic) and methodology techniques can explain the higher frequency of participants with CMV viremia compared to ours, that is, 37% versus 12%.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Although those authors suggest the existence of such a relationship, it is not causal. Moreover, they found no relationship between CMV viral load in saliva and active disease 17 . Immunosuppressive protocol, reduced sample size, pediatric patients, type of transplantation (renal and hepatic) and methodology techniques can explain the higher frequency of participants with CMV viremia compared to ours, that is, 37% versus 12%.…”
Section: Discussioncontrasting
confidence: 62%
“…A study with 27 pediatric kidney‐liver transplant patients reported that herpesviruses were detected in 88.9% and 37.0% of the samples of saliva and blood, respectively, with the majority (22/27) having more than one virus at the same time 17 . A similar pattern was also found in our study, but contrary to our results, those authors found a relationship between salivary excretion and CMV viremia.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Oral CMV DNA shedding is frequent in allo‐HSCT recipients and may precede the detection of CMV DNA in blood . Recently published data suggest that this may indeed be the case in pediatric solid organ transplant recipients, in which patients with CMV DNA detectable in their saliva are more likely to develop CMV DNAemia . Based on these studies, in addition to assessing the frequency of CMV DNA detection in saliva, we examined the kinetics of oral CMV DNA shedding and that of plasma CMV DNAemia in a cohort of allo‐HSCT and assessed to what extent serial screening of saliva specimens for the presence of CMV DNA by using a highly sensitive real‐time PCR would allow anticipation of the occurrence of plasma CMV DNAemia.…”
Section: Discussionmentioning
confidence: 99%